Hydrogen energy: development, advantages, and challenges in the era of transition to a sustainable society - Ibrayeva, А.Е. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
The article analyzes the development potential of hydrogen energy in Kazakhstan. The approach of considering international experience and determining the role of Kazakhstan in the global hydrogen market is chosen. At the same time, the main global development incentives are taken into account, such as environmental policy and the projected growth in demand for environmentally friendly hydrogen. Being the smallest element of the chemical table, hydrogen requires a special technical and regulatory framework for production, storage, transportation and application, which are insufficient in Kazakhstan today. On the other hand, the existing oil and gas infrastructure and significant potential for the development of renewable energy sources in the country are a significant advantage for starting work. In the context of growing global demand for green hydrogen, Kazakhstan not only has the possibility of large-scale production for export, but also needs an environmentally friendly product to reduce carbon emissions in the energy sector and narrowly focused industry. At the same time, given the increased likelihood of water scarcity and a number of serious technical limitations in working with hydrogen, the development of a new sector of the economy will require a phased strategic approach.